Análise cinética da resposta imune humoral contra a proteína recombinante SAG2A em pacientes com Toxoplasmose aguda - Santana, Silas Silva (2011)
Recombinant proteins from Toxoplasma gondii have been used in several experimental models, as well as for serodiagnosis of human toxoplasmosis, particularly to differentiate acute from chronic phases of the infection. In the present study, we evaluated the kinetics of IgM, IgA, and IgG isotypes, in addition to IgG1 and IgG3 subclasses, by testing sequential serum samples from patients with acute toxoplasmosis. It was carried out immunoassays by using SAG2A recombinant antigen and soluble antigen of Toxoplasma (STAg). The avidity of IgG1 antibody was assessed using slot blot assay. Additionally, a ratio between IgG1 and IgG3 subclasses (IgG3:IgG1) was determined and evaluated its degree of association with levels of IgM and IgA specific for STAg and the avidity index of IgG1 specific for SAG2A. The results showed a decreasing kinetic profile for SAG2A and STAg for IgM and IgA. The kinetic profile for the IgG antibody was increasing for both antigens. Compared to the avidity for IgG1, it was observed that sera from an early stage showed a low average avidity of IgG1 for SAG2A while the same samples showed intermediate mean avidity of IgG1 when STAg was used as antigen. In a later phase, the average avidity observed was high for STAg and intermediate for SAG2A in the same tested sera suggesting that SAG2A may be a promising tool for the detection of avidity. Associations between IgG3/IgG1 and specific IgM and IgA levels for STAg and the avidity index of specific IgG1 for SAG2A were found, and together these parameters could be used as valuable tools in the diagnosis of human toxoplasmosis, especially in situations when the determination of different phases is critical.